Dorda V. O. System organization of lexical and semantic units of american student slang - Dorda V. O. (Philological Treatises, 2020)
The paradigmatic, epidigmatic and syntagmatic relations are being analyzed in the system of American student slang. The paradigmatic relations consist in changing of the initial archiseme to another one. This results in including of the new lexeme into the other lexical and semantic field. The epidigmatic relations are based on different interpretation and derivative and semantic dependences. The syntagmatic relations are characterized by the semantic change of a lexeme depending on its lexical and context compatibility.